EFFECT OF MALELO SANDAL SALT WITH HN03 TO THE EFFICIENCY OF CRYSTAL IMPLEMENTATION - Siti Sulastri; Susila Kristianingrum; Retno Arianingrum (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2004)
The objective of this study was to investigate the effect of soaking nitrate acid of Malelo sand to adsorption efficiency of chromium (Cr). The Malelo sand was prepared by soaking in nitric acid with variation of concentration were 17,5: 35 and 70% for 24 hours at room temperature. The adsorption efficiency of chromium was determined based on concentration of chromium residue after adsorption. which measured using Atomic Absorption Spectrophotometer (AAS). The characterization of Malelo sand determined using FTIR and XRD. The result indicated that the mean ofadsorption efficiency of chromium on Malelo sand without preparation and soaking in nitrate acid with variation concentration 17.5: 35 and 70% were 91,36: 92,40: 92,72 and 94,004% respectively.